Consensus Paper: Pathological Role of the Cerebellum in Autism - Fatemi, S. Hossein; Aldinger, Kimberly A.; Ashwood, Paul; Bauman, Margaret L.; Blaha, Charles D.; Blatt, Gene J.; Chauhan, Abha; Chauhan, Ved; Dager, Stephen R.; Dickson, Price E.; Estes, Annette M.; Goldowitz, Dan; et al. (Cerebellum (London, England), 2012)
There has been significant advancement in various aspects of scientific knowledge concerning the role of cerebellum in the etiopathogenesis of autism. In the current consensus paper, we will observe the diversity of opinions regarding the involvement of this important site in the pathology of autism. Recent emergent findings in literature related to cerebellar involvement in autism are discussed, including: cerebellar pathology, cerebellar imaging and symptom expression in autism, cerebellar genetics, cerebellar immune function, oxidative stress and mitochondrial dysfunction, GABAergic and glutamatergic systems, cholinergic, dopaminergic, serotonergic, and oxytocin-related changes in autism, motor control and cognitive deficits, cerebellar coordination of movements and cognition, gene–environment interactions, therapeutics in autism, and relevant animal models of autism. Points of consensus include presence of abnormal cerebellar anatomy, abnormal neurotransmitter systems, oxidative stress, cerebellar motor and cognitive deficits, and neuroinflammation in subjects with autism. Undefined areas or areas requiring further investigation include lack of treatment options for core symptoms of autism, vermal hypoplasia, and other vermal abnormalities as a consistent feature of autism, mechanisms underlying cerebellar contributions to cognition, and unknown mechanisms underlying neuroinflammation.